Neurotrophic Receptor Tyrosine Kinase 2 (NTRK2) Alterations in Low-Grade Gliomas: Report of a Novel Gene Fusion Partner in a Pilocytic Astrocytoma and Review of the Literature - Siobhan S. Pattwell; Eric Q. Konnick; Yajuan J. Liu; Rebecca A. Yoda; Laligam N. Sekhar; Patrick J. Cimino (Hindawi Limited, 2020)
Pilocytic astrocytoma is a low-grade glial neoplasm of the central nervous system (CNS) that tends to occur in the pediatric population and less commonly presents in adults. Hereditary pilocytic astrocytoma is often associated with germline genetic alterations in the tumor suppressor NF1, the gene responsible for the syndrome neurofibromatosis type 1. Sporadic pilocytic astrocytoma frequently harbors somatic alterations in BRAF, with rare pilocytic astrocytomas containing alterations in FGFR1 and NTRK2. NTRK2 encodes for the protein tropomyosin receptor kinase B (TrkB), which is a neurotrophin receptor with high affinity for Brain-Derived Neurotrophic Factor (BDNF), and plays a role in several physiological functions of neurons, including cell survival and differentiation. In this report, we describe a novel PML-NTRK2 gene fusion occurring in an adult sporadic pilocytic astrocytoma and review the biology and implications of specific NTRK2 mutations occurring in CNS neoplasms.